Community-Based Science Education on Sexual Violence Prevention: A Case Study at St. Xaverius Catholic High School Gunungsitoli Bintang Laut Teluk Dalam - Blasius S. Yesee; Leoni Intan F. Luahambowo; Dominikus Doni Ola; Alfons Seran; Sitepanus Zebua (Postgraduate, University of Mataram, 2025)
Sexual violence in schools is a serious and growing concern that demands a comprehensive educational and preventive response. This study aims to introduce science-based education on the recognition and prevention of sexual violence among senior high school students through a community intervention model. A case study approach was conducted in two private high schools in the Nias Islands, involving five lecturers from the Pastoral High School and 154 students from grades X and XI. The intervention included socialization sessions, knowledge transfer, and structured assistance from school principals and teachers. The educational content was enriched by legal perspectives from the Nias and South Nias Police Departments, psychological insights, and child protection material from the Center for Child Protection Studies. The findings reveal strong student engagement, active participation in discussions, and increased awareness regarding the forms and dangers of sexual violence. The program encouraged critical reflection and fostered a sense of responsibility among students. Overall, this community-based science education initiative shows promising outcomes in empowering students as agents of change and in promoting a safer, more supportive school environment.